(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study investigates the influence of hydrothermal ZnO and curry leaf extract-synthesized ZnO nanoparticles (green ZnO) on the physiology and growth of tomato (Solanum lycopersicum) plants. The prepared nanomaterials were characterized by FTIR, XRD for structural analysis and SEM for surface morphology. Hydrothermal ZnO, characterized by larger and less porous particles 10 nm, provided moderate improvements in germination, root elongation, chlorophyll content, and yield, primarily through basic zinc supplementation. In contrast, curry leaf extract ZnO, with smaller, porous, flower-like nanostructures 10 nm coated with bioactive phytochemicals, significantly enhanced seed germination (15–20%), root and shoot development, photosynthetic efficiency, and fruit yield (12–18%). The improved performance of green ZnO is attributed to its higher bioavailability, controlled zinc release, and activation of antioxidant pathways, making it a sustainable and eco-friendly nanofertilizer for enhancing tomato growth and productivity.